MEMBANGUN KESALEHAN SOSIAL DALAM INTEGRASI PAI DAN REALITA SOSIAL - Rahmah, Ivana Maulia; Sunhaji (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Amidst rapid social dynamics and the overwhelming flow of information, Islamic Religious Education (PAI) faces the challenge of shaping a young generation that is not only spiritually obedient but also socially pious. This article examines the importance of integrating PAI with social reality to develop individuals who are both religious and socially aware. Using a descriptive qualitative approach and a case study at Sabilul Muttaqin Mosque in Pecikalan Hamlet, Wangon, Banyumas, this research explores the implementation of social values in religious practices. The findings indicate that PAI integrated with values such as empathy, justice, solidarity, and responsibility can effectively strengthen students’ character in a contextual manner. Programs such as regular religious study sessions, free markets, free haircuts, and free health checks serve as effective media for grounding Islamic values in real life. The mosque functions not only as a place of worship but also as a center for empowerment and character education. Support from religious leaders, mosque youth, and the local community has transformed the mosque into a synergistic space where religious texts meet social context. These findings reinforce that social piety can only grow when PAI is participatory, applicable, and relevant to the needs of the community. This kind of integration offers a strategic solution to protect the younger generation from moral decline while strengthening education's role as an agent of social transformation.